2018
DOI: 10.20546/ijcmas.2018.710.135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sub-Surface Drainage System on Soil Chemical Properties and Yield of Rice Crop at Head Region of Tungabhadra Command Area

Abstract: Studies on subsurface drainage were carried out on silty clay and clay soils in Gundur village from 2015 to 2016. The mean pH of samples ranged from 8.16 to 8.35 before sowing and 8.21 to 8.41 after harvesting and before sowing the electrical conductivity ranged from 10.92 to 14.65 dS m -1 and 9.28 to 13.68 dS m -1 after harvesting. Similarly, the Ca 2+ +Mg 2+ and Na + values were in the range of 34.01 to 37.14 and 10.47 to 12.89 Meq/100g before sowing of crops, after harvesting of the crops results obtained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Among collected water samples analyzed from manhole, about 50 percent samples are safe and remaining 50% are of unsafe for irrigation respectively. Mallika (2017) [8] however reported generally zero RSC of drain discharge waters at different villages viz., Chagabhavi (tail region of TLBC), Gundur (head region of TLBC) and Mallapur village (Middle region of TLBC) during kharif 2015 and 2016. With one-time sampling, Prasanna et al (2011) [13] and Kumar (2014) [7] reported that the RSC values of the majority surface/stream/bore well water samples were under good category (<1.25 me L -1 ) indicating feasibility for irrigation purpose.…”
Section: Residual Sodium Carbonate (Rsc)mentioning
confidence: 97%
See 1 more Smart Citation
“…Among collected water samples analyzed from manhole, about 50 percent samples are safe and remaining 50% are of unsafe for irrigation respectively. Mallika (2017) [8] however reported generally zero RSC of drain discharge waters at different villages viz., Chagabhavi (tail region of TLBC), Gundur (head region of TLBC) and Mallapur village (Middle region of TLBC) during kharif 2015 and 2016. With one-time sampling, Prasanna et al (2011) [13] and Kumar (2014) [7] reported that the RSC values of the majority surface/stream/bore well water samples were under good category (<1.25 me L -1 ) indicating feasibility for irrigation purpose.…”
Section: Residual Sodium Carbonate (Rsc)mentioning
confidence: 97%
“…The drain discharge or drainage water outflow varied from 0.75 to 1.21 mm day -1 with a mean value of 0.94 mm day -1 . Mallika (2017) [8] reported the average drain discharge during kharif 2015 and 2016 ranged from 0.08 to 0.75, 0.11 to 0.85, 0.12 to 0.99, mm d -1 in the M1 (60 m spacing), M2 (50 m spacing), M3 (40 m spacing), respectively at Mallapur village (Middle region of TLBC) site. Similarly, at Chagabhavi village (Tail region of TLBC), the drain discharge varied from 0.19 to 1.22, 0.18 to 1.18 and 0.20 to 1.28 and mm d -1 in 60, 50 and 40 m spacing respectively.…”
Section: Drain Discharge (Dd)mentioning
confidence: 99%
“…PA studies have shown that subsurface drainage systems reduce soil reactions and soil salinity (Shrikanta et al, 2019), collectors are under extreme pressure in the Nile delta during summer months (Rashed et al, 2004), and salt-affected soil improves of its hydraulic conductivities (Mallika et al, 2019). Malota and Senzanje (2016) reported that the drainage design criteria of three different drainage applications in a drainage system were lower than the applied design levels, and the observed average water table depth and drainage discharge were unsatisfactory.…”
Section: O T S C L é Smentioning
confidence: 99%
“…PA studies have shown that subsurface drainage systems reduce soil reactions and soil salinity (Shrikanta et al, 2019), collectors are under extreme pressure in the Nile delta during summer months (Rashed et al, 2004), and salt‐affected soil improves of its hydraulic conductivities (Mallika et al, 2019).…”
Section: Introductionmentioning
confidence: 99%